Sky Parenting on Children's Prayer Discipline Education: A Case Study of a Family Living Around the Great Mosque of Balaibaru Kuranji Padang, West Sumatra - Agustina, Linda; Tago, Mahli Zainuddin (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This study aims to analyze the influence of sky parenting on children's prayer discipline education, focusing on case studies of families living around the Balaibaru Kuranji Grand Mosque, Padang, West Sumatra. The sky parenting approach is essential to improve children's prayer discipline because it provides consistent support, guidance, and example in religious practice. The research method uses a qualitative approach with a case study approach. In addition, this study used qualitative methods such as in-depth interviews with parents and children to gain deeper insight into their experiences in applying the sky parenting approach. After collecting the data, the research analysis stage begins with data categorization and coding to identify emerging patterns and themes related to sky parenting practices and children's prayer disciplines. Furthermore, this study uses a thematic analysis approach to explore the relationship between sky parenting practices and children's prayer disciplines. Finally, the study compiles the findings into a coherent narrative and produces conclusions that support or reject the research hypothesis. This study provides deep insight into the importance of sky parenting in shaping children's prayer discipline in the mosque environment. The implications of this research could be helpful for communities, religious institutions, and education practitioners to develop more effective strategies in guiding children to vital spiritual obedience through sky parenting.